PANoptosis: Cross-Talk Among Apoptosis, Necroptosis, and Pyroptosis in Neurological Disorders - Li P; Gao Y; Tao Z; Mu Z; Du S; Zhao X (Journal of Inflammation Research)
Pengpeng Li,1– 3,* Yangyang Gao,4,* Zhenxing Tao,2,5 Zhenqian Mu,1,2 Shiqing Du,2 Xudong Zhao3 1Wuxi School of Medicine, Jiangnan University, Wuxi, Jiangsu, People’s Republic of China; 2Department of Neurosurgery, Jiangnan University Medical Center, Wuxi, Jiangsu, People’s Republic of China; 3Department of Neurosurgery, The Affiliated Wuxi No. 2 People’s Hospital of Nantong Medical University, Wuxi, Jiangsu, People’s Republic of China; 4Ningxia Medical University, Yinchuan, People’s Republic of China; 5Wuxi Neurosurgical Institute, Wuxi School of Medicine, Jiangnan University, Wuxi, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xudong Zhao, Email 9862022148@jiangnan.edu.cnAbstract: Cell death mechanisms play a critical role in organismal development and homeostasis, primarily categorized into energy-dependent programmed cell death (PCD) and energy-independent necrotic cell death. PCD, regulated through various forms such as apoptosis, necroptosis, pyroptosis, ferroptosis, and autophagic cell death, is essential for maintaining tissue stability and eliminating abnormal cells. Dysregulation of PCD is associated with numerous diseases, including cancer and neurodegenerative disorders. Recent studies have revealed extensive crosstalk and coordination among classical cell death pathways, leading to the identification of a novel programmed cell death mode termed PANoptosis. PANoptosis involves the dynamic assembly of the PANoptosome complex, which simultaneously activates apoptosis, pyroptosis, and necroptosis pathways in response to pathogen infection or tissue damage. In neurological diseases, PANoptosis exhibits dual roles: it can eliminate pathogen-infected cells but may also exacerbate neuroinflammation and neuronal death, contributing to the progression of neurodegenerative disorders. This review critically evaluates the molecular mechanisms of PANoptosis, its dual roles in neurological diseases (eg, Alzheimer’s disease, Parkinson’s disease, stroke, and glioma), and potential therapeutic strategies targeting PANoptosis, including small-molecule inhibitors, genome editing, and delivery technologies. By addressing conflicting evidence and outstanding questions, this review aims to provide a comprehensive framework for future research and clinical applications. Future research should focus on elucidating the molecular regulatory networks of PANoptosis, developing specific inhibitors, and advancing clinical applications to provide novel insights into the precise treatment of neurological diseases.Keywords: PANoptosis, neurodegenerative diseases, PANoptosome, inflammasomes, neuroprotection